Diazoxide Post-conditioning Activates the HIF-1/HRE Pathway to Induce Myocardial Protection in Hypoxic/Reoxygenated Cardiomyocytes - Chen, Xi-Yuan; Wang, Jia-Qi; Cheng, Si-Jing; Wang, Yan; Deng, Meng-Yuan; Yu, Tian; Wang, Hai-Ying; Zhou, Wen-Jing (Frontiers in Cardiovascular Medicine, 2021)
Background: Previous studies have shown that diazoxide can protect against myocardial ischemia-reperfusion injury (MIRI). The intranuclear hypoxia inducible factor-1 (HIF-1)/hypoxia-response element (HRE) pathway has been demonstrated to withstand cellular damage caused by MIRI. Although diazoxide postconditioning showed protective effect on rat cardiomyocytes in hypoxic-reoxygenation injury, it remains unclear whether it is correlated with the HIF-1/HRE pathway. Methods: An isolated cardiomyocyte model of hypoxia-reoxygenation injury was established. Prior to reoxygenation, cardiomyocytes underwent postconditioning treatment by diazoxide, and 5-hydroxydecanoate (5-HD), N-(2-mercaptopropionyl)-glycine (MPG), or Dimethyloxallyl Glycine (DMOG) followed by diazoxide. At the end of reoxygenation, ultrastructural morphology; mitochondrial membrane potential; levels of IL-6, TNF-α, reactive oxygen species (ROS), and HIF-1α; and the downstream gene’s mRNA and protein levels were analyzed to detect the protective mechanism of diazoxide postconditioning. Results: Diazoxide postconditioning could activate the HIF-1/HRE pathway to induce myocardial protection. When 5-HD inhibited mitoKATP opening and MPG cleared the ROS, the diazoxide effect could be eliminated. The mitoKATP and ROS in early reoxygenation phase were key to activate the HIF-1/HRE pathway. Conclusion: Diazoxide postconditioning promotes the opening of mitoKATP to generate an appropriate amount of ROS to activate the HIF-1/HRE pathway that, in turn, induced myocardial protection.